Bias induced spin transitions of spin crossover molecules: the role of charging effect. Issue 11 (3rd March 2017) - Hao, Hua; Jia, Ting; Zheng, Xiaohong; Zeng, Zhi
Abstract : A new mechanism is proposed to understand the recently observed spin transition of spin crossover molecules from low spin to high spin under bias voltages and it is closely related to one additional electron on the spin crossover molecules. Abstract : The spin transition of spin crossover molecules induced by bias voltages from low spin to high spin was observed recently and several mechanisms were suggested to understand it. However, these mechanisms fail to explain the dependence of spin transitions on the bias polarity in experiments and thus may still be questionable. Based on a first-principles study, we propose that the bias-induced spin transition is triggered by a charging effect, namely, the filling of the lowest unoccupied molecular orbital of spin crossover molecules. Our proposal is substantiated by three steps: (1) the spin transition from low spin to high spin can be achieved by charging the isolated spin crossover molecules with one extra electron; (2) in molecular junctions, the charging of spin crossover molecules can be realized by electron transfer from electrodes to molecules under finite bias; (3) more importantly, the electron transfer is dependent on the bias polarity due to asymmetrical couplings of the sandwiched molecule with two electrodes. This mechanism satisfactorily explains the bias-polarity dependent spin transitions in experiments [Miyamachi et al., Nat. Commun., 2012, 3, 938; Gopakumar et al., Angew. Chem. Int. Ed., 2012, 51, 6262].